Strategi Kesantunan Guru dalam Pembelajaran sebagai Penanaman Etika Komunikasi Siswa Sekolah Dasar - Roatin, Syuhri; Sudiyana, Benedictus; Pratiwi, Veronika Unun (GERAM (Gerakan Aktif Menulis), 2026)
Research on teacher politeness strategies generally focuses on linguistic forms in classroom interactions, while studies linking these strategies to cultivating students' communication ethics in primary school Indonesian language learning remain limited. This study aims to describe the teacher's language politeness strategies and uncover the cultivation of students' communication ethics through these strategies. A qualitative case study approach was applied at SDN 01 Gawanan Colomadu, involving a third-grade teacher and students. Data were collected through observations of classroom interactions, semi-structured interviews with the teacher, and documentation of teaching modules and video recordings. Data analysis involved reduction, coding of positive and negative politeness utterances, thematic presentation, and drawing conclusions via triangulation. The results showed that the teacher’s politeness strategies included collective greetings, inclusive pronouns, specific praise, empathetic politeness markers, indirect instructions, softening particles, and personal reprimands without negative labeling. The cultivation of students' communication ethics was reflected in respectful attitudes, the confidence to voice opinions politely, the use of courteous expressions, the ability to accept corrections, and emotional control. These findings confirm that teacher language politeness strategies are an effective pedagogical practice for sustainably shaping students' communication ethics.